Twelve-Year Outcomes of Pterygium Excision with Conjunctival Autograft versus Intraoperative Mitomycin C in Double-Head Pterygium Surgery - Wong, Ian Y. H.; Yeung, Emily F. Y.; Yuen, Hunter K. L.; Li, Emmy Y. M.; Wong, Raymond L. M.; Chan, Tommy C. Y.; Jhanji, Vishal (Journal of ophthalmology, 2015)
Purpose. The study aims to compare the long-term outcome of conjunctival autograft (CAU) and mitomycin C (MMC) in double-head pterygium surgery. Methods. This is a follow-up study of a comparative interventional trial. Thirty-nine eyes of the 36 patients with double-head pterygium excision in the original study 12 years ago were recruited for clinical assessment. Seven out of the 36 patients were lost. In the original study, each eye with double-head pterygium was randomized to have pterygium excision with CAU on one “head” (temporal or nasal) and MMC on the other “head.” All patients were invited for clinical assessment for conjunctival bed status and the presence of pterygium recurrence in the current study. Results. There was no significant difference between the size, morphology, and type of pterygium among the two treatment groups. The recurrence rate of CAU group and MMC group 12 years after excision was 6.3% and 28.1%, respectively (P=0.020). Among eyes without recurrence, the conjunctival bed was graded higher in the MMC group than the CAU group (P=0.024). Conclusion. The use of conjunctival autograft has a significantly lower long-term recurrence rate than mitomycin C in double-head pterygium surgery.